Fathers’ Involvement During the Baby’s Third Month - Piccinini, Cesar Augusto (2012)
This study investigated the involvement of fathers when their baby was three months old. Participants included 38 primiparous fathers with ages from 20 to 40 years. The fathers’ interviews were content analyzed, based on three dimensions of father involvement: interaction, accessibility and responsibility. Fathers reported their involvement in many care activities, although not always routinely. They also mentioned worries and a much involvement in decisions related to care, education and baby’s health. However, fathers considered their participation less than desired due to work-related time restrictions. These results indicated an increase in father involvement during the baby’s third month and the need for emotional support for the fathers during this family transition.